Over a million students use our free study notes to help them with their homework
2x + y = 7
3x - y = 8
You cannot find x and y using only one equations, but using both you can! So first you have use algebra to make both equations = y. Try this for the first equation by r...
So we start off with (11-w)/4 = 1+w
First of all, we will multiply both sides by 4 to make the '/4' disappear. This gives us 11-w = 4+4w
Then move all the w's to one side of the equation to ...
The rule we use here is (ab)c = abc
Therefore, (k3)2 = k6
We have a quadratic equation since the highest power of x is 2. Therefore, we can use the quadratic formula, which we recall to be: x = [- b ± √(b² - 4ac) ] / 2a In accordance with the formula, we set a =...
When each term has the same base, add the indices that are multiplied. Then subtract the indices that are divided.
a^5 x a^16 / a^ 4 = a^(5+16) / a^4
= a^ 21 / a...
←
627
628
629
630
631
→
Internet Safety
Payment Security
Cyber
Essentials